Implementation and ethical issues of an eHealth-facilitated integrated care model in stem cell transplantation: A qualitative process evaluation study - Linda Wienands; Julia Krumme; Sabina De Geest; László Kovács; Alexandra Teynor; Sabine Valenta; Lynn Leppla (Digital Health)
Introduction eHealth-facilitated integrated care models (eICMs) offer promising enhancements to healthcare delivery in stem cell transplantation, but entail implementation and ethical challenges. While qualitative process evaluation methodologies can effectively address such issues through interdisciplinary collaboration, no previous studies have integrated approaches from implementation science and applied ethics into eICM evaluations. Objective Exploring an integrated approach to the qualitative process evaluation of a stem cell transplantation eICM (SMILe–ICM), our objectives were threefold: (1) assess the current SMILe–ICM's implementation through stakeholder perceptions; (2) examine relevant ethical issues; and (3) develop strategies to mitigate identified implementation and ethical challenges. Methods Semistructured individual interviews were conducted with 12 patients and 3 relatives. Additionally, 8 clinicians in total participated in two focus groups. Data analysis followed an inductive-deductive thematic approach built on interpretative frameworks from implementation science and medical ethics and supported by ethical consultations. Results We isolated three main themes, centered on the patient's treatment journey and recovery, to explain patients’, their relatives’ and clinicians’ perceptions regarding the SMILe–ICM. While the SMILe–ICM was generally viewed as valuable, perspectives varied regarding standardized procedures, including eHealth, and care coordination practices. These themes encompass implementation and ethical issues related to individual, intervention, inner setting, and outer setting factors, leading to the development of 17 implementation strategies. Conclusion This study provides nuanced insights into patient- and provider-level eICM implementation and ethical challenges. By identifying these issues early, the integrated research design and resulting strategies facilitated well-informed, timely solutions.